Henneguya polarislonga n. sp. (Cnidaria: Myxosporea) parasitizing Astyanax lacustris (Lütken, 1875) with an insight on its life cycle - Jorge, Maurício [UNESP]; Vieira, Diego Henrique Mirandola Dias [UNESP]; Zago, Aline Cristina [UNESP]; Franceschini, Lidiane [UNESP]; Silva, Reinaldo José da [UNESP] (Elsevier, 2022)
Henneguya polarislonga n. sp. is described from the gills of Astyanax lacustris (Lütken, 1875) (Characiformes, Characidae) from streams of the Middle Paranapanema River, Upper Paraná River basin, in the São Paulo State, Brazil. The proposed new species is supported by a combination of morphological and molecular characterization (partial fragment of the SSU rDNA). Thirty specimens of A. lacustris were analyzed and myxospores were found in the gill lamellae of one specimen (Prevalence = 3.3%). Henneguya polarislonga n. sp. was morphometrically and genetically distinct from other Henneguya spp. previously described in Astyanax spp., mainly differing in the total length and caudal appendages length of the mature myxospores. Comparative analysis of the SSU rDNA sequences revealed that Seisactinomyxon-type actinospores previously reported parasitizing oligochaetes are developmental stages of the life cycle of Henneguya polarislonga n. sp. (similarity of 99.9%). This is the first time that an actinospore and a myxospore are correlated through molecular analysis in Brazil, contributing to the knowledge of the myxozoan ecology and biodiversity.
Keywords: Biodiversity; Freshwater; Ichthyoparasitology; Myxobolidade; Taxonomy